Vasodilatation in response to repeated anodal current application in the human skin relies on aspirin-sensitive mechanisms - Durand, S (Blackwell Science Inc, 2002)
The vasodilatation resulting from prolonged square-wave monopolar current application as used in iontophoresis is assumed to rely on an axon reflex. Involvement of prostaglandins in the anodal current-induced vasodilatation remains unclear. We tested the hypothesis that prostaglandins participate in a sensitisation mechanism to current application rather than as direct vasodilators. In healthy volunteers, laser Doppler flowmetry (LDF) was recorded in the forearm during and following isolated or repeated 0.1 mA transcutaneous anodal current applications, using deionised water as a vehicle. Segmented current applications of 6 or 12 mC resulted in an LDF increase twice that observed following current applications of comparable total charge delivered all at once (P < 0.05). Following a 1 min anodal application, a slow and prolonged LDF drift occurred (slope: 0.3 ± 0.5 arbitrary units min(−1)). When the same current application was repeated after intervals of 5 and 20 min, an abrupt vasodilatation occurred, with maximal LDF amplitude of 53.5 ± 34.0 and 48.2 ± 19.1 arbitrary units, respectively. Pretreatment with 1 g oral aspirin abolished the abrupt vasodilatation to repeated current application but not the initial slow drift. We suggest that vasodilatation occurs through two parallel pathways: (1) a slow progressive drift of LDF of limited amplitude insensitive to aspirin pretreatment, and (2) an abrupt vasodilatation probably resulting from afferent fibre activation, appearing if a preliminary sensitisation by current application is performed. Sensitisation lasts for at least 20 min, and is blocked by aspirin, suggesting participation of prostanoids.